PENGEMBANGAN KAPASITAS KELEMBAGAAN PETANI (KASUS DI PROVINSI JAWA TENGAH) - Sapja Anantanyu (Caraka Tani: Journal of Sustainable Agriculture, 2008)
Agriculture development program is so difficult to reach small farmers. Economic indicators, agricultural infrastructures, and goverment policy often cause small farmers to economical and social marginalized. Farmer less possession in land, marginal rate of return in agriculture sector, agriculture policy which nonalignment to farmer make more difficult to increase their inncome. On the other side, farmer’s institutions which are expected be able to strengthen the farmer position to face the existing problems not effectively yet.The purpose oh this research in to identify the determinant factors in capacity buliding of farmer’s institution and to formulate an appropriate strategy of extention program. This research was conducted at three district in Center Java Province, they were: Klaten, Grobogan, and Karanganyar. Data collected through interview of 405 respondents whose member of farmer’s institution, 48 local leaders, and informans. The result shows that member’s participation in farmer’s institution represent their collective awareness caused easier to manage their farm. The level of member’s participation in farmer’s institution was influenced by their capacities level, internal and external factors of farmer, e.i: (a) social and economical status of farmer, (b) needs of farmer, (c) learning experience of farmer, (d) local leadership, (e) outsider role, and (f) the quality of extention. Quality of agricultural extension, directly and indirectly, influence to farmer capacities. It increase their participation in farmer’s institution and push their institution effectiveness.